Desenvolvendo a análise crítica em alunos do ensino médio por meio da estatística e a realidade econômica do Brasil: um estudo com base na teoria significativa da aprendizagem - Silva, Fernanda Levandoski da (2019)
The present investigation starts from the conception that the Statistic is an indispensable tool for the understanding and critical interpretation of the citizen with respect to the world to his, assuming a necessary role to the understanding of its contents and not only the domain of writing and reading. From these conceptions, arises a question that constitutes the central question of the research that originated the present study: How can students of the High School use Statistics to understand the index of economic development in the surrounding Region of the Municipalities of Alto Uruguai, through of a didactic sequence involving statistics? In this context, this dissertation, chose the basic subjects of Statistics as a theme of the didactic proposal and its main objective was to investigate the contribution of a sequence didactics of Statistics with a focus on the analysis of data on the economic development of the Alto Uruguai region for the learning of the concepts of the area in the High School. This didactic sequence was methodologically structured in the Theory of Meaningful Learning proposed by David Paul Ausubel and implemented with a group of students of the second series of High School of a state public school in the municipality of Erechim, RS. Of character qualitative and participant, the research had as instruments for data collection the logbooks elaborated by the teacher/researcher throughout the implementation of the proposal, the comparative pre-test results and a post-test applied in the first and last date and a dissertation prepared by the students at the end of the proposal's implementation. The results show that a didactic sequence that starts from the reality of the students structured from the assumptions of the Theory of Meaningful Learning can favor the occurrence of signs of significant learning of Statistics subjects, since the results of the students in the post-test presented higher accuracy indexes than in the pre-test and that the logbook and textbook records will demonstrate student acquisition of knowledge and the application of subjects in other contexts. The educational product that accompanies the study refers to the elaborate didactic sequence and is made available in the form of teacher support material on the program site and the Portal <http://educapes.capes.gov.br/handle/capes/432171>.